Chinese Architecture and Metaphor: Song Culture in the Yingzao Fashi Building Manual - Lin, Francis Chia-Hui (Asian studies review, 2014)
The author also discusses the faithfulness of the text, as the YZFS is a form of historiography. [...]the text, the author argues, had a transit in its production process of translating the past into a selective historical record, eventually being presented as an official ideological standard of aesthetic harmony.